Internet literacy among the older adults: a case study in information searching / Nazima Muhammad Nazir - Muhammad Nazir, Nazima (2017)
Literacy is an important concept in determining the level of skills and knowledge in a particular field. Internet literacy is a capability to use the Internet for many purposes such as information gathering. On the other hand, the older adults are a group of people who assumed to be left out in terms of Internet usage. Their skills of using the Internet is in grey area. The aim of this study is to understand the Internet literacy among the older adults and to see what capabilities they had in manipulating the Internet. A qualitative method was used in this study. Data collection process was gathered through a face-to-face interview with the participants, a user testing session to assess the participants' skills, and observations of the participants' behaviours during user test being conducted. Thematic analysis was used as the main guideline to analyse rich data that been gathered. The study suggested that the older adults have skills in using the Internet, even though were limited to the functional literacy. It is hoped that this study could give more insights in improving the older adults' skills and knowledge in maximizing the Internet facilities.